The TCA pathway is an important player in the regulatory network governing Vibrio alginolyticus adhesion under adversity - Lixing eHuang; Li eHuang; Qingpi eYan; Yingxue eQin; Ying eMa; Mao eLin; Xiaojin eXu; Jiang eZheng (Frontiers in Microbiology, 2016)
Adhesion is a critical step in the initial stage of Vibrio alginolyticus infection; therefore, it is important to understand the underlying mechanisms governing the adhesion of V. alginolyticus and determine if environmental factors have any effect. A greater understanding of this process may assist in developing preventive measures for reducing infection. In our previous research, we presented the first RNA-seq data from V. alginolyticus cultured under stress conditions that resulted in reduced adhesion. Based on the RNA-seq data, we found that the Tricarboxylic acid cycle (TCA pathway) might be closely related to adhesion. Environmental interactions with the TCA pathway might alter adhesion. To validate this, bioinformatics analysis, qPCR, RNAi and in vitro adhesion assays were performed, while V. alginolyticus was treated with various stresses including temperature, pH, salinity and starvation. The expression of genes involved in the TCA pathway was confirmed by qPCR, which reinforced the reliability of the sequencing data. Silencing of these genes was capable of reducing the adhesion ability of V. alginolyticus. Adhesion of V. alginolyticus is influenced substantially by environmental factors and the TCA pathway is sensitive to some environmental stresses, especially changes in pH and starvation. Our results indicated that 1) the TCA pathway plays a key role in V. alginolyticus adhesion: 2) the TCA pathway is sensitive to environmental stresses.